Nine new species of Megaselia Rondani (Diptera: Phoridae) from the Seychelles - Disney, R. Henry L. (Zootaxa, 2006)
Nine new species o f Megaselia are descr ibed from th e Seychelles, some of which are s ibling species of M. mera (Collin), whose hitherto unkno wn male is described. The ne w species ar e M. birdensis, M. dilatimana, M. falsoluta, M. furculae, M. fuscamplicosta, M. pseudomera, M. seychellesensis, M. vannusetarum an d M. vitiomera. Megaselia dilatimana is reco r ded f r om Aldabra and Arabia as well.